The Perfections of God in the Theology of Karl Barth: A Consideration of the Formal Structure - Eric Titus (Kairos (English Ed.))
This treatment of the perfections of God in the theology of Karl Barth serves as an introduction and summary of Barth’s thinking on this topic as found in Church Dogmatics II.1. The focus of the article is weighted to the formal side of Barth’s construction while not ignoring material considerations. As such, the author considers Barth’s understanding of God as the One who loves in freedom, general characteristics of Barth’s understanding of divine perfections, and more specifically the dialectical dyadic paradigm used by Barth in his construction.